2014
DOI: 10.1152/ajpregu.00425.2013
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide release from contracting skeletal muscle in pulmonary TNF-α overexpression mice

Abstract: Chronic obstructive pulmonary disease (COPD) often results in increased levels of tumor necrosis factor-α (TNF-α), a proinflammatory cytokine, which circulates in the blood. However, it is not clear whether pulmonary TNF-α overexpression (a COPD mimic) induces excessive reactive oxygen species (ROS) formation in skeletal muscle and thereby may contribute to the muscle impairment often seen in COPD. We hypothesized that ROS generation in contracting skeletal muscle is elevated when there is TNF-α overproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…O 2 ·− and other relatively stable ROS, such as hydrogen peroxide (H 2 O 2 ) have been implicated in activation signaling pathways in neighboring cells by regulating stress-related proteins such as MAPK and p53 under low doses of irradiation exposure [27, 28]. The mechanism for the increase of extracellular O 2 ·− is complex and could be associated with an enhanced inflammatory response such as TNF-α overexpression [29]. Other ROS which are derived from O 2 ·− , such as H 2 O 2 , may cause damage towards the normal or less-irradiated cells by giving sufficient perfusion time, exacerbating bystander effects [18, 27, 30].…”
Section: Discussionmentioning
confidence: 99%
“…O 2 ·− and other relatively stable ROS, such as hydrogen peroxide (H 2 O 2 ) have been implicated in activation signaling pathways in neighboring cells by regulating stress-related proteins such as MAPK and p53 under low doses of irradiation exposure [27, 28]. The mechanism for the increase of extracellular O 2 ·− is complex and could be associated with an enhanced inflammatory response such as TNF-α overexpression [29]. Other ROS which are derived from O 2 ·− , such as H 2 O 2 , may cause damage towards the normal or less-irradiated cells by giving sufficient perfusion time, exacerbating bystander effects [18, 27, 30].…”
Section: Discussionmentioning
confidence: 99%
“…So the question is whether circulating or lung-derived TNF-/ would have an impact on muscle function. In a transgenic mouse model overexpressing TNF-/ in the lung, TNF-/ impaired peripheral skeletal muscle function due to excessive formation of superoxide in contracting skeletal muscle [36,37]. However, a study of 426 COPD patients over a 3-year period found that TNF-/ levels were associated with muscle loss only in patients who were cachectic at entry into the study; the authors concluded that inflammation is a consequence rather than a cause of initial loss of fat-free mass [38].…”
Section: Copdmentioning
confidence: 99%
“…In addition, CS has been associated with elevated ROS production by leukocytes in the airways of both acute and chronic smokers (21). Subsequently, this production is stimulated by the release of ROS by neutrophils and macrophages, in conjunction with the inflammatory response (such as TNF-␣ production) to CS (78,146). Furthermore, excess CS-induced ROS cannot be neutralized by endogenous antioxidants, ultimately resulting in oxidative stress-induced damage (21), which has been frequently demonstrated in animal models.…”
Section: Role Of Reactive Oxygen Species In Copdmentioning
confidence: 99%